Resident and Distributed Models of Control Systems for Technological Machines - A. A. Goncharov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Basic structural and functional components of the control system project are control algorithm, control program, principle scheme, scheme of electrical equipment arrangement, schemes of driving mechanisms, etc. The system of predicate formulae (SPF) as a formalized resident model has been selected to be the gist of the project.Method of evental modeling for SPF, due to which results are reflected on the enumerated non-formalized parts of the project, is realized. This modeling is called distributed.